2008
DOI: 10.1159/000115639
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Carpal Tunnel Syndrome: Is There a Causal Relationship?

Abstract: Objectives: Obesity is defined as a risk factor for carpal tunnel syndrome (CTS). In this study, the presence or absence of recovery in median nerve conduction velocities after weight loss in obese patients was assessed in order to determine whether excess weight or other factors influence the higher prevalence of CTS in obese patients. Methods: Patients with body mass indexes (BMIs) ≧30 were included in the study. CTS symptoms, age, gender, height, body weight, and concomitant diseases were evaluated. Nerve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…In the second hypothesis, the CTS symptoms would not respond to weight loss, as was found at present. Corroborating these findings, Kurt et al 11 studied CTS in 92 obese patients, who underwent a three-month dietary program for weight loss, and found no changes in nerve conduction studies, signs or symptoms after that intervention. Also, Shiri et al 13 demonstrated an association of CTS with dyslipidemia, hypertension and cardiac arrhythmia in individuals between 30 and 34 years of age, and with coronary artery disease, valvular heart disease and carotid intimal thickness in subjects aged 60 years or more.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the second hypothesis, the CTS symptoms would not respond to weight loss, as was found at present. Corroborating these findings, Kurt et al 11 studied CTS in 92 obese patients, who underwent a three-month dietary program for weight loss, and found no changes in nerve conduction studies, signs or symptoms after that intervention. Also, Shiri et al 13 demonstrated an association of CTS with dyslipidemia, hypertension and cardiac arrhythmia in individuals between 30 and 34 years of age, and with coronary artery disease, valvular heart disease and carotid intimal thickness in subjects aged 60 years or more.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 94%
“…It can therefore be concluded that obesity is associated with CTS, but weight loss in bariatric surgery is not sufficient to improve its repercussions in daily life. The higher prevalence of CTS in obese individuals is already well known in the literature [6][7][8][9][10][11][12][13] . Similarly, Moghtaderi et al 8 conducted a case-control study examining risk factors for CTS and demonstrated that BMI, age and anthropometric data of the wrist were higher in patients with CTS than in controls.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with right CTS right hand was dominant but there was no correlation like this for the left side. If we look up the literature investigating the relation between obesity and CTS, it is mentioned that obesity is a risk factor for CTS in most of the studies [3,4,5]. De Azevedo et al [6] investigated the profile of patients on sick leave with CTS and reported obesity with a ratio of 44% among these patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated and determined a relation of obesity especially with CTS, which is one of the upper extremity entrapment neuropathies [7][8][9][10][11]. Likewise, a triggering effect of obesity on the cubital tunnel syndrome was reported [12,13].…”
Section: Introductionmentioning
confidence: 99%